Medical management of first trimester missed miscarriage: the efficacy and complication rate. (4th July 2019) - Serdinšek, Tamara; Reljič, Milan; Kovač, Vilma
Abstract: Our aim of the study was to evaluate the efficacy and complication rate of our inpatient medical management protocol for missed miscarriages. Three-hundred and ninety women hospitalised at our tertiary centre because of a missed miscarriage/anembryonic pregnancy in 2012–2013 were included in this retrospective study. The women underwent either a low (until 9 + 0 weeks of gestation) or high gestational age (from 9 + 1 until 15 + 6 weeks of gestation) management protocol. The success rate, curettage in the first 48 hours after the procedure, the complication rate and the factors that might influence these outcomes were evaluated. The overall success rate was 83.3%. The curettage in the first 48 hours after the procedure was performed in 7.4% of the patients and was more often in the high gestational age protocol. Complications that required another outpatient visit or hospitalisation occurred in 9% of the patients. Higher beta-hCG values 14 days after the procedure and the absence of evacuation of products of conception during hospitalisation were associated with a higher complication rate. IMPACT STATEMENT: What is already known on this subject? As much as 10–20% of clinically recognised pregnancies end in a spontaneous abortion. A missed miscarriage and a blighted ovum represent a form of spontaneous abortion, which has long been treated with surgical evacuation. However, nowadays, medical management represents a well-established alternative with very high success rates and is considered as an equivalent and safe method that is also very well accepted by patients. What do the results of this study add? According to our results, a medical management of a first trimester missed miscarriage and a blighted ovum is very effective with an overall success rate of 83.3% and a very low percentage of curettage in the first 48 hours after the procedure (7.4%). Our study was also able to identify higher beta-hCG values 14 days after procedure and absence of evacuation of products of conception during hospitalisation as risk factors for complication occurrence. What are the implications of these findings for clinical practice and/or further research? Our study helps to identify patients who are at greater risk for developing complications after the medical management of a first trimester missed miscarriage.